PENGARUH PENAMBAHAN TEPUNG KUNYIT DALAM RANSUM TERHADAP KONSUMSI PAKAN, PERTAMBAHAN BOBOT BADAN HARIAN, DAN KONVERSI PAKAN KAMBING JAWARANDU - Novi Eka Wati; Mahmud Syarifudin; Kunaifi Wicaksana; Lusia Komala Widiastuti (Wahana Peternakan, 2023)
The aim of the study was to determine the effect of adding turmeric flour in the ration on feed consumption, daily body weight gain and feed conversion of Jawarandu Goats. This research was conducted in Adi Jaya Village, Terbanggi Besar District, Central Lampung Regency. The design used in this study was a completely randomized design (CRD) consisting of 3 treatments with each treatment repeated 4 times, while the treatments were as follows: P0 = ration without the addition of turmeric flour, P1 = ration + 0.25% turmeric flour, P2 = Ration + 0.5% turmeric flour for 30 days. They were fed BNR complete feed as control ration were containing 12% crude protein and 70% total digestible nutrient. The addition of Turmeric flour (Curcuma domestica) up to 0,50% on ration had no significant effect (P>0.05) on feed consumption, body weight gain and feed conversion ratio of Jawarandu goat. Keywords: Jawarandu goat, Turmeric, Feed consumption, Daily body weight gain, Feed conversion